The effect of cortisol in early pregnancy on postpartum depressive symptoms - Małgorzata Sobol; Inna Hryhorchuk; Elżbieta Plucińska; Paulina Szczepaniak; Agata Błachnio; Janusz Stasiniewicz; Marek K. Sobol (Scientific Reports)
Abstract The first months after childbirth are a tremendous challenge for women and, consequently, a time when women’s mental health problems often arise. Knowledge of the prenatal predictors of these problems is of fundamental importance in preventing them. This study aimed to test whether first trimester hair cortisol influenced maternal postpartum depressive symptoms. The women (N = 75) were tested twice: in the first trimester of pregnancy and within three months after giving birth. In the first trimester, they had hair samples taken and were examined using a sociodemographic survey and questionnaires: the Edinburgh Postnatal Depression Scale (EPDS), the Perceived Stress Scale (PSS-10), and the Zimbardo Time Perspective Inventory. After delivery, women completed a survey about the course of delivery and their child’s health, EPDS, and PSS-10. Low hair cortisol concentration in the first trimester was a predictor of a high level of postpartum depressive symptoms. This relationship was mediated by fatalistic time perspective. The results suggest that low hair cortisol concentration in the first trimester of pregnancy indicates a high probability of postpartum depression, and that low levels of cortisol may be associated with passivity, a sense of lack of control, and helplessness.